Mekanisme Kerja Prostaglandin Analog Terhadap Jalur Uveosklera dan Efeknya Untuk Menurunkan Tekanan Intra Okular - Julian Tanri; Daberto Andrias; Edgar Christoffer Hasoloan; Yunia Gracia Sesa; Santi Anugrahsari (Jurnal MedScientiae, 2023)
High Intraocular Pressure (IOP) which is > 21 mmHg could damage optical nerves which could results in blindness. High IOP is often caused by an obstruction of the eye ball fluid circulation which is called the Aquoeus Humour. In this era, decreasing IOP is still a main focus during therapy. The application of this therapy however is still a challenge because of the lack of drug obedience especially because of the side effects. This review is intended to provide patient a complementary medication to fulfill their therapy. Literature references are acquired through online science database search engine using Google Scholar, Science Direct, and Pubmed. This review includes 9 journals, with all articles conlcuded that prostaglandin analogues are the best choice in order to decrease IOP. Prostaglandin analogue functions as to repair the outflow of the uveoscleral pathway. Latanoprost 0.005% and latanoprostene bunod 0.024% are the best choice of prostaglandin analogue as a therapy for glaucoma, ocular hypertension, and many other diseases that increases IOP. The side effects of the prostaglandin analogue don’t appear often in patients and the side effects were shown to be mild which is considered preferable and safe decision for therapy.